HYDRO-CLIMATIC EVENTS DURING THE LITTLE CLIMATIC OPTIMUM IN ROMANIA - ELENA TEODOREANU (Revue Roumaine de Géographie)
Our knowledge of the climate during the Little Climatic Optimum (8th–14th centuries) in this country comes from some historical studies of climatic events occurring in countries around or nearRomania (Hungary, the Italian Peninsula, Ukraine, the Balkan Peninsula and the region around Constantinople), found in foreign chronicles, French, German, and Russian, as well as in some notes of foreign travellers in that territory. The records speak mostly of harsh winters, especially early in the interval considered, with rivers and the Black Sea frozen, or rainy summers,with floods, but also of some very warm winters, with tree in blossoms in January, and long, hot and dry summers. Some of these extreme events led to famine, pestilence, and high morbidity.